2010
DOI: 10.1210/en.2010-0638
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Endocannabinoid Signaling Reduces GABAergic Synaptic Transmission to Gonadotropin-Releasing Hormone Neurons

Abstract: Cannabinoids suppress fertility via reducing hypothalamic GnRH output. γ-Aminobutyric acid (GABA)A receptor (GABAA-R)-mediated transmission is a major input to GnRH cells that can be excitatory. We hypothesized that cannabinoids act via inhibiting GABAergic input. We performed loose-patch electrophysiological studies of acute slices from adult male GnRH-green fluorescent protein transgenic mice. Bath application of type 1 cannabinoid receptor (CB1) agonist WIN55,212 decreased GnRH neuron firing rate. This acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
125
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 63 publications
11
125
0
1
Order By: Relevance
“…As previously mentioned, cannabinoid receptors are closely related to neurons in the hypothalamus and GnRH release has been shown to be inhibited in males by AEA and THC through interaction with GABA and other systems [58,[80][81][82]. This reduction in gonadoliberins can cascade to the rest of the HPG axis as to be discussed subsequently (see Table 1).…”
Section: Effect On the Hpg Axismentioning
confidence: 76%
See 2 more Smart Citations
“…As previously mentioned, cannabinoid receptors are closely related to neurons in the hypothalamus and GnRH release has been shown to be inhibited in males by AEA and THC through interaction with GABA and other systems [58,[80][81][82]. This reduction in gonadoliberins can cascade to the rest of the HPG axis as to be discussed subsequently (see Table 1).…”
Section: Effect On the Hpg Axismentioning
confidence: 76%
“…This action could be prevented by a specific CB1 antagonist (SR141716) [56,57]. Farkas and coworkers furthermore demonstrated that endocannabinoid activates CB1 which, in turn, inhibits spontaneous gamma aminobutyric acid (GABA) release [58]. Postsynaptic GABA receptors, located on GnRH neurons, are not activated, and as a consequence, GnRH is not released.…”
Section: Ecs and The Hypothalamus-pituitary-gonadal Axismentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of CB1 in this putative GABAergic input system to GnRH neurons may explain our recent electrophysiological and morphological data that retrograde endocannabinoid signaling reduces GABAergic afferent drive onto GnRH neurons via the activation of presynaptic CB1 receptors (Farkas et al, 2010). In that study we have provided evidence that GnRH neurons produce 2-arachidonoylglycerol (2-AG).…”
Section: Gabaergic Neurons Expressing Cb1 Mrnamentioning
confidence: 92%
“…Its presynaptic action via CB1 decreases GABA release, which, in turn, reduces postsynaptic GABAA-R signaling and inhibits the firing activity of GnRH neurons (Farkas et al, 2010).…”
Section: Gabaergic Neurons Expressing Cb1 Mrnamentioning
confidence: 99%